Efficient Tabu search method for basic sequencing problem - Ismail, Zuhaimy; Wan Ibrahim, Wan Rohaizad; Ahmad, Maizah Hura; Sze , San Nah; Mahpol, Khairil Asmani (Universiti Teknologi Malaysia, 2005)
Lot-size is the clustering of items for transportation or manufacturing processes occurring at the same time. The issue in lot-size problem is to design production processes so that the feasible production quantities are equal to customer demand quantities and the timing of production is such that inventory positions are almost zero. In this study, we explore the multilevel lot-size and scheduling problem. It is on a multi-level capacitated lotsize problem or known as the multi-level lot-size problem with bottlenecks. Two models were introduced to solve the multi-level lot-size problem. They were the model developed by Billington et. al. (1986). It is model with a simple heuristic as proposed by Bilal Toklu and J.M. Wilson (1991), and as proposed by Alf Kimms (1997). A comparative study between these models was also given with both models formulated as an integer-programming problem. Here we represent a study on the implementation of these two models with case studies to demonstrate the systems work.